The Use of Different Type of Sand in Calibration of Sand Replacement Test - Azman, Faizal; Yusma Khairul, Hasnawi; Yasin, Harith; Suwandi, Amir Khan (Multidisciplinary Applied Research and Innovation, 2022)
Sand is a granular material that contains organic matter and is made up of finely split rock and mineral particles. 3 type of sand was selected to check the sand availability as replacement for the standard sand that used in sand replacement test in laboratory. The aim of this study is to identify different type of sand that can replace standard sand used in the sand replacement test. Various sampling sand was taken in Selangor and Melaka states. The sea sand, river sand and quarry sand along with standard sand was tested in various aspect such as sieve analysis, moisture content, particle density, relative density, direct shear, and in-situ field density using sand replacement test method. The result of study showed that sea sand displayed the most potential as replacement for the standard sand. The various sand is expected to have same comparison in aspect with the standard sand used in sand replacement test.